Associated Factors of Surgical Glove Damages in Orthopedic Surgeries - Jazinidorcheh, Saeed (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Sterile surgical gloves protect patients from the surgical team members’ microbial flora of the hands, and mutually, the members of the surgical team from pathogens of the patient’s body. Damage of surgical gloves during each surgical procedure is one of the major concerns. There are a lot of risk factors and related issues associated with the damage of gloves that the results of other studies about them in some cases are consistent and in some cases inconsistent with each other. The aim of this study was to investigate the rate of surgical glove damages based on various factors in orthopedic surgery. Materials and Methods: In this descriptive-analytic study, 384 surgical gloves (192 pairs) were the study samples. The gloves were all made of the same material, and they were consisted of two layers. The gloves were selected based on a simple sampling study method. The study environment was the orthopedic and nerve operating room in Kashani Hospital associated with Isfahan’s Medical Sciences University. The study population included the gloves wore by the scrubbed individuals during foot and hand orthopedic plating operations. Data collection tools were comprised of questionnaires and checklists all constructed by the researcher. Questionnaire contained demographic information, surgery type, and the operation team members, and the checklists covered items pertaining to the surgical glove damages. The present study made use of Water Leak Test to evaluate whether the gloves have been damaged or not. To analyze the data, descriptive statistics tests and analytical statistical tests were applied, and the data were further inspected in the SPSS software, ver. 22. Results: The results of this study showed that there was a significant relationship between the type of surgery, the role of people in procedure, the gender of the surgical team, the location of damage on the gloves, the glove layer, the dominant hand of people, and the rate of damage of the surgical gloves, among different issues (*P < 0.05), and factors such as the number of scrubbed staff in surgery, the surgical team experience, and the size of surgical gloves did not have a significant relationship with the rate of surgical glove damages (*P > 0.05). Discuss and Conclusion: Considering to risk factors that damage to surgical gloves by the surgical team, can reduce the number of needle sticks or transmission of infection between patients and them. According to the results, it is suggested that the surgical team during surgery should seek more attention to their dominant hands and in the areas contacting with the surgical instruments and the patient’s body, including the thumb and index finger. Furthermore, due to the higher rate of surgical gloves damages in implanting plates into the femur, it is recommended to put on two layers gloves or routine changing of them during these surgical procedures.